Disease suppression in Ganoderma-infected oil palm seedlings treated with Trichoderma harzianum - Mohd Zainudin, Nur Ain Izzati; Abdullah, Faridah (Czech Academy of Agricultural Sciences, 2008)
Disease suppression in Ganoderma-infected oil palm seedlings treated with a conidial suspension of Trichoderma harzianum FA 1132 was tested in plant house conditions to determine the effectiveness of the fungus as a biocontrol agent. The highest efficacy of control was achieved by treatment right after artificial infection; the total number of infected plants was reduced to give the lowest disease severity index (DSI) value of 5.0%, compared to the infected and non-treated control that had the highest DSI of 70.0%. After conidia suspension of FA 1132 was applied, the colony forming ability by Trichoderma in the soil was dramatically increased, but decreased after some time. Results of the present study are a useful reference basis for further tests in the field and large scale production trials.